Keparahan Penyakit Hawar Daun Jingga pada Beberapa Galur dan Varietas Padi - Sudir Sudir; Suparyono Suparyono (Universitas Gadjah Mada, 1996)
Disease severity of orange leaf blight (OLB) was observed on several different genotypes of rice in Sukamandi, Pusakanegara, and Batang Research Station during the dry season of 1993. Results indicated, that except in Batang, under natural condition OLB developed well in all locations. Different responses were observed among rice genotypes, indicated that different level of resistance to OLB are available in rice germplasm. Out of 230 rice genotypes observed in bastard population, 4 were rated resistant (disease severity 8.5-10%), 7 were moderately resistant (disease severity 15-20%). No resistant or moderately resistant genotypes were observed among 24 genotypes in yields trials, 16 in adaptability trials, 12 in promising lines demonstration, and 49 in hybrid rice trials.